INTEGRATION OF DYNAMIC CASE MANAGEMENT SYSTEMS IN BEHAVIORAL HEALTH: A NOVEL PEGA-BASED FRAMEWORK FOR ENHANCED CARE DELIVERY - Phani Kumar Praturi (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article examines implementing a comprehensive Pega-based case management system in behavioral healthcare settings, addressing critical challenges in care coordination, crisis management, and patient engagement. The article systematically analyzes the platform's integration, focusing on its dynamic workflow capabilities, artificial intelligence-driven decisioning, and interoperability with existing healthcare systems. The article demonstrates significant improvements in care team communication, crisis response times, patient engagement metrics, and operational efficiency through a detailed examination of implementation frameworks and outcomes. The article suggests that automated case management systems can transform behavioral healthcare delivery by streamlining workflows, enhancing patient monitoring, and enabling data-driven decision-making. This article contributes to the growing literature on healthcare technology integration while providing practical insights for healthcare organizations seeking to modernize their behavioral health management systems. The article also highlights future directions for technology enhancement in behavioral healthcare, including telepsychiatry integration and advanced analytics capabilities.